2014
DOI: 10.1107/s2053230x14018962
|View full text |Cite
|
Sign up to set email alerts
|

Structure of anAspergillus fumigatusold yellow enzyme (EasA) involved in ergot alkaloid biosynthesis

Abstract: The Aspergillus fumigatus old yellow enzyme (OYE) EasA reduces chanoclavine-I aldehyde to dihydrochanoclavine aldehyde and works in conjunction with festuclavine synthase at the branchpoint for ergot alkaloid pathways. The crystal structure of the FMN-loaded EasA was determined to 1.8 Å resolution. The active-site amino acids of OYE are conserved, supporting a similar mechanism for reduction of the /-unsaturated aldehyde. The C-terminal tail of one monomer packs into the active site of a monomer in the next as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This is the case of e.g. NerA, EasA from Aspergillus fumigatus (PDB ID 4qnw [ 56 ]), GYE from Gluconobacter oxydans (PDB ID 3wjs).…”
Section: Resultsmentioning
confidence: 99%
“…This is the case of e.g. NerA, EasA from Aspergillus fumigatus (PDB ID 4qnw [ 56 ]), GYE from Gluconobacter oxydans (PDB ID 3wjs).…”
Section: Resultsmentioning
confidence: 99%
“…242 Crystal and NMR structures of FgaOx3 demonstrated that the reduction of the C8]C9 double bond of 150 by FgaOx3 facilitates intramolecular cyclization between the aldehyde and the amine moieties. 243,244 FgaFS further reduces the cyclic iminium product to form 151, which was conrmed by the co-incubation of recombinant FgaOx3 and FgaFS and also by a step-wise reaction with FgaOx3 followed by FgaFS in the presence of NADH. 245 In the absence of FgaFS, 150 is converted into a dominant product of E/Z isomers, via an FgaOx3mediated reaction.…”
Section: Reviewmentioning
confidence: 99%
“…61 In addition, FgaOx3 reduces the double band between C8 and C9 of chanoclavine-I aldehyde, and the reduction facilitates an intramolecular reaction between the aldehyde and the amine moieties to allow the formation of festuclavine, which was recently conrmed by the crystal structure resolution of the FMN-loaded FgaOx3. 60,62,63 Wallwey et al reported that the oxidoreductase FgaFS in A. fumigatus reduced the cyclic iminium product formed by FgaOx3 to produce festuclavine. 64 In an in vitro reaction system, festuclavine was formed when chanoclavine-I aldehyde was incubated with the recombinant FgaOx3 and FgaFS simultaneously or as a tandem-reaction with FgaOx3 before FgaFS in the presence of NADH (Fig.…”
Section: Biosynthetic Pathway Of Ergoclavinesmentioning
confidence: 99%